Family Support for The Care of High-Risk Pregnant Women During The Covid-19 Pandemic - Herlina Herlina (LPPM STIKes Muhammadiyah Ciamis, 2021)
In the health sector, maternal mortality remains a major issue in Indonesia. High-risk mothers are one of the leading causes of death. If a mother has 4T and is too pregnant, she meets the risk criteria: young, old, frequent, and a lot In this study, a cross-sectional approach was used, and quota sampling was used to select a 50-person sample. High-risk pregnant women's compliance with pregnancy checks in the Sungai Betung Health Center work area was significantly correlated with family support, with a significant value (p) of 0.001 0.05. The correlation coefficient (p) is 0.619, indicating that pregnant women in the Sungai Betung Health Center work area are more likely to comply with pregnancy checks if their families are supportive. During the Covid-19 pandemic, it was discovered that prenatal screenings for high-risk pregnant women were associated with family support. This study suggests that healthcare providers and families should pay close attention to high-risk pregnant women, particularly those with four (4T), who should not have their pregnancies checked too frequently, too frequently, or too close to home.